2017
DOI: 10.3389/fmed.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix (Permacol®) for Heterologous Immediate Breast Reconstruction after Skin-Sparing Mastectomy in Patients with Breast Cancer: A Single-Institution Experience and a Review of the Literature

Abstract: ObjectiveSkin-sparing mastectomy (SSM) with immediate heterologous reconstruction is a safe oncological option in surgical therapy of early breast cancer. Permacol® is an acellular dermal matrix (ADM) placed between the implant and the skin to improve lower pole projection and implant coverage. The aim of our study was to evaluate the outcome with a focus on patient satisfaction after 6 months and to analyze physical changes of ADM.Methods10 patients who underwent SSM with Permacol® were analyzed retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(15 reference statements)
0
5
0
1
Order By: Relevance
“… 54 By facilitating an optimal breast pocket, ADMs help to obtain symmetrical coverage, enhance the aesthetic outcome, decrease pain from pectoralis muscle mobilisation and reduce scarring. 57 , 62 Limited capsule contracture and scarring may also be attributed to the decreased inflammatory response associated with ADMs. 63 , 64 Additionally, it is more difficult for scar tissue or capsules to develop on the ADM surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 By facilitating an optimal breast pocket, ADMs help to obtain symmetrical coverage, enhance the aesthetic outcome, decrease pain from pectoralis muscle mobilisation and reduce scarring. 57 , 62 Limited capsule contracture and scarring may also be attributed to the decreased inflammatory response associated with ADMs. 63 , 64 Additionally, it is more difficult for scar tissue or capsules to develop on the ADM surface.…”
Section: Resultsmentioning
confidence: 99%
“…2,50,51 While individual reports vary, aggregate data indicate that complications are rare. [52][53][54][55][56][57] A systematic review of 1039 breast reconstructions with either PADM or HADM showed low overall rates of skin and nipple necrosis (11% and 5%, respectively), infection (12%), hematoma (1%) and seroma (5%), with only 9% of patients requiring reoperation. 52 This success may be attributed to ADMs' ability to fully integrate into host tissue with neovascularisation, cell repopulation and lack of inflammatory cells observed at both short-and long-term follow-up.…”
Section: Plastic and Reconstructive Surgery-burnmentioning
confidence: 99%
“…Moreover, combining ADM with expander two-stage reconstruction is considered to be significantly more expensive than using autologous/tissue expander combinations [39]. Tissue integration of an ADM is related to vascular ingrowth of the matrix, and the CEUS in vivo evaluation by Parvizi et al reported enhancement in the ADM after a month [40]. Ballesio et al attested with a US examination partial integration of ADM at six months of follow-up and complete integration at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…A matriz é colocada entre o implante e a pele para melhorar a projeção do polo inferior mamário e a cobertura do implante com o intuito de evitar o uso de retalhos miocutâneos, bem como prevenir deformações mamárias, contraturas e exposição do implante. Outra vantagem dessa matriz é seu baixo custo em relação a outras MDAs (KNABBEN et al, 2017).…”
Section: Discussionunclassified